2021
DOI: 10.3390/cancers13153688
|View full text |Cite
|
Sign up to set email alerts
|

From Micro to Long: Non-Coding RNAs in Tamoxifen Resistance of Breast Cancer Cells

Abstract: Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer mortality among women. Two thirds of patients are classified as hormone receptor positive, based on expression of estrogen receptor alpha (ERα), the main driver of breast cancer cell proliferation, and/or progesterone receptor, which is regulated by ERα. Despite presenting the best prognosis, these tumors can recur when patients acquire resistance to treatment by aromatase inhibitors or antiestrogen such as tamoxifen (Tam). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 188 publications
(211 reference statements)
0
11
0
Order By: Relevance
“…The potential diagnostics of circulating miRNAs, especially from exosomes (EV-miRNAs), has already been discussed ( Liu et al, 2019 ; Ozawa et al, 2020b , 2020a ). In addition, other non-coding RNAs (nc-RNAs) are emerging as potential biomarkers as long non-coding RNAs ( Gradia et al, 2017 ; Barazetti et al, 2021 ; Mathias et al, 2021 ) and circular RNAs (circ-RNAs) ( Qian et al, 2018 ; Ameli-Mojarad et al, 2021 ; de Palma et al, 2022 ). Ameli-Mojarad et al (2021) showed a higher expression of circRNAs in BC tissues than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The potential diagnostics of circulating miRNAs, especially from exosomes (EV-miRNAs), has already been discussed ( Liu et al, 2019 ; Ozawa et al, 2020b , 2020a ). In addition, other non-coding RNAs (nc-RNAs) are emerging as potential biomarkers as long non-coding RNAs ( Gradia et al, 2017 ; Barazetti et al, 2021 ; Mathias et al, 2021 ) and circular RNAs (circ-RNAs) ( Qian et al, 2018 ; Ameli-Mojarad et al, 2021 ; de Palma et al, 2022 ). Ameli-Mojarad et al (2021) showed a higher expression of circRNAs in BC tissues than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently many miRNAs have been found to be associated with the progression of tamoxifen resistance of breast cancer cells [89][90][91], however, the miRNAs involvement in…”
Section: Discussionmentioning
confidence: 99%
“…Recently many miRNAs have been found to be associated with the progression of tamoxifen resistance of breast cancer cells [89][90][91], however, the miRNAs involvement in the resistance development is still unclear. Here we have found that some miRNAssuppressors of oestrogen signalling are overexpressed in the exosomes of the tamoxifenresistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the changes in mRNA expression, alterations in micro RNA content have also been observed. A recent review listed about 75 micro RNAs associated with tamoxifen resistance [ 17 ]. For example, mir-375 [ 18 ], mir-519a [ 19 ] miR-181b [ 20 ], miR-363, [ 21 ] or miR-451 [ 22 ] were functionally associated with tamoxifen resistance.…”
Section: Introductionmentioning
confidence: 99%